"Souvenirs" from Vukovar: Tourism and Memory within the Post-Yugoslav Region - Patrick Naef (Via@)
This paper aims at exploring the developing tourism in certain places of collective remembrance in the post-Yugoslav region, specifically that of Vukovar, a locality situated in Slavonia in the east of Croatia, which acquired the status of a martyred city after the war.